The Other Women's Movement : Workplace Justice and Social Rights in Modern America - Cobble, Dorothy Sue (Book collections on Project MUSE., 2004)
American feminism has always been about more than the struggle for individual rights and equal treatment with men. There's also a vital and continuing tradition of women's reform that sought social as well as individual rights and argued for the dismantling of the masculine standard. In this much anticipated book, Dorothy Sue Cobble retrieves the forgotten feminism of the previous generations of working women, illuminating the ideas that inspired them and the reforms they secured from employers and the state. This socially and ethnically diverse movement for change emerged first from union.